Recent developments in perovskite-based precursor inks for scalable architectures of perovskite solar cell technology - Trystan Watson (Sustainable Energy and Fuels, 2022)
The progressive enhancements in solar-to-electrical conversion within the past decade have allowed organic–inorganic lead halide perovskite-based solar cell (PSC) technology to become a competitive candidate for creating affordable and sustainable electricity. This review highlights the developments in fabricating advanced precursor inks of organic–inorganic lead halide perovskite-based light harvesters for large-area perovskite solar cell technology. One of the key characteristics of this promising photovoltaic technology includes solution processing, which offers possibilities to scale up lab-sized solar cell devices into large-area perovskite solar modules comprising unique device architectures. These have been realized in recent years for their deployment in various applications such as building-integrated photovoltaics or internet of things (IoT) devices. In this regard, the presented overview highlights the recent trends that have emerged in the research and development of novel perovskite precursor ink formulations, and it also discusses their contribution toward demonstrating efficient, scalable, and durable PSC technology to create electricity and energize futuristic applications. Various reports were included aiming to showcase the robust photovoltaic performance of large-area perovskite solar modules in a variety of device configurations, hence providing a brief overview of the role of state-of-the-art scalable precursor ink development in transforming unstable lab-sized solar cells into robust, low-cost perovskite solar cell technology that can be scaled up to cover much larger areas.